Mathematical Model of Human Papillomavirus (HPV) Dynamics With Double-Dose Vaccination and Its Impact on Cervical Cancer - Henok Desalegn Desta; Getachew Teshome Tilahun; Tariku Merga Tolasa; Mulugeta Geremew Geleso (Discrete Dynamics in Nature and Society)
We develop a deterministic mathematical model to investigate the transmission dynamics of human papillomavirus (HPV) and its impact on cervical cancer. The model divides the population into six classes: susceptible individuals St, first vaccinated individuals Vt, permanently immunized individuals Pt, HPV-infected individuals IHPVt, HPV-infected individuals with cervical cancer Ct, and recovered individuals Rt. The study includes analyzing the stability of the disease-free and endemic equilibriums. The analysis reveals that the disease-free equilibrium is locally asymptotically stable when the average number of secondary HPV-infectious individuals (R0) is less than one and unstable when it is greater than one. A stable local endemic equilibrium occurs when the average number of secondary HPV-infectious individuals exceeds one, indicating the persistence of the disease in the community. The value of R0 is derived using the next-generation matrix approach, revealing that HPV-infected individuals persist in the community. MATLAB 2015a is used to represent the simulation findings visually. The numerical simulation suggests that increasing vaccination coverage and the recovery rate helps to reduce HPV-infected individuals while reducing the contact rate can effectively control disease transmission.